2021
DOI: 10.3390/su13073900
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Microstructure and Sustainability of Ultra-High-Performance Concrete Using Ultrafine Calcium Carbonate and High-Volume Fly Ash under Different Curing Regimes

Abstract: In current practice, the performance-based concrete mix (PBCM) approach has become quite popular because it enhances the quality of materials that are fundamentally necessary for a particular situation. In the present study, experimental analysis is performed to determine the optimal mechanical properties and microstructural characteristics of concrete for sustainable development and cost effectiveness. Specifically, a mixture of high-volume fly ash (FA) and ultrafine calcium carbonate (UFCC) is investigated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 32 publications
(37 reference statements)
0
5
0
Order By: Relevance
“…For that reason, the effective combination of FA and SF as a partial replacement for cement and an enhancer for strength and durability becomes a common practice [27][28][29][30][31][32][33][34][35]. The ternary combination of SF (10%) with FA increases its compressive strength compared to the reference binary with FA by about 145% [30].…”
mentioning
confidence: 99%
“…For that reason, the effective combination of FA and SF as a partial replacement for cement and an enhancer for strength and durability becomes a common practice [27][28][29][30][31][32][33][34][35]. The ternary combination of SF (10%) with FA increases its compressive strength compared to the reference binary with FA by about 145% [30].…”
mentioning
confidence: 99%
“…This material is classified as Type I in ASTM C150 [32]. The properties of Ordinary Portland Cement were investigated by Azmee et al [33] and many others. The chemical properties of the local Portland Cement used in this study are given in Table 3.…”
Section: Cementmentioning
confidence: 99%
“…Such additions of eco-friendly materials contributed clearly to enhancing the environment and specifications of concrete. Azmee et al [42] prepared UHPC for the requirements of many construction applications and indicated that UHPC needed a high cement content. Accordingly, they studied the process of lowering the cement content in the UHPC using fly ash and ultrafine CaCO 3 .…”
Section: Introductionmentioning
confidence: 99%